Association between different anthropometric indicators and body image in adolescents - Felden, Érico Pereira Gomes (2021)
Introduction and purpose: The perception of body image reflects on how people see and perceive their body. The objective is to investigate the relationship between body image perception and different indicators of nutritional status in adolescents. Materials and Methods: a cross-sectional, population-based study was carried out in the city of Santa Maria-RS, Brazil, in 2009. A total of 1176 adolescents, with a mean age of 16.24 (1.39), enrolled in high school were investigated. Body image perception was identified through the analysis of silhouettes and associated with measures of body mass, height, waist circumference (WC), body mass index (BMI) and nutritional status in adjusted models.  Discussion: the prevalence of overweight and obesity confirms data presented in the literature. Results: the prevalence of obesity was 6.1% and 4.6% for boys and girls, respectively. 35.4% of the boys were dissatisfied with the thinness and 50.1% of the girls were dissatisfied with the excess weight. The adjusted analysis model presented the main predictors of perception of real body image (PICR) to CC (60% of explanation) in boys and BMI (53% of explanation) in girls. Conclusions: high prevalence of dissatisfaction with body image was identified. Boys were more dissatisfied with thinness, because of the desire to increase muscle mass and girls with excess weight. CC and BMI were the main predictive variables of RIPR for boys and girls, respectively. Health education measures regarding body knowledge for high school adolescents were recommended.